Sonido bestial (2017)
"This investigation tries to rescue salsas culture in the city of Cali, taking as a reference the 70s period, where "La Sucursal del Cielo" (colloquial name for Cali) opens its heart to this special dance. Using interviews, visual documentation, old photographs, older bibliography, among other tools; this project looks forward to define the feeling salsa causes in the "Caleños" . The process finally leads to a materialization of the feeling, creating a conceptual collection of shoes, that can be continued as a premium brand." -- Tomado del Formato de Documento de Grado.